Catalyst for synthesizing thiophanate-methyl and preparation method thereof
By using pretreatment zeolite as a catalyst for the carrier and active components during the methylthioprotein synthesis process, the problem of excessive reaction is solved, and methylthioprotein synthesis with high purity and high yield is achieved, which shortens the synthesis cycle and reduces the generation of side reactions.
Patent Information
- Application Number
- CN202411922219.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
In the prior art, the reaction of methylthioglycinide is too severe during the synthesis of methylthioglycinide, resulting in liquid splashing and increased side reactions, resulting in a decrease in product yield and purity.
The catalyst including pretreatment zeolite as a support and the active component is used to stabilize and continuously release the active component through the combination of the support and the active component, and avoid the occurrence of violent reactions and side reactions.
The gentle progress of the reaction was achieved, the synthesis purity and yield of methylthiobrazin was improved, the synthesis cycle was shortened, and the generation of side reactions was reduced.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, in particular to a catalyst for synthesizing methyl thiophanate and a preparation method thereof. Background Art
[0002] Methyl thiophanate, whose chemical name is 1,2-bis-(3-methoxycarbonyl-2-thioureido)benzene and whose trade name is methyl thiophanate, is a white crystal in its pure form with a melting point of 172°C (decomposition). It is almost insoluble in water, benzene, xylene, and ether, but soluble in methanol, acetone, and chloroform, and easily soluble in acetonitrile and dimethylformamide. It is unstable in acidic and alkaline media, stable to light, and of low toxicity. It has the characteristics of high efficiency, spectral and systemic absorption, and has both protective and therapeutic effects.
[0003] Methyl thiophanate is mainly obtained by catalytic synthesis using methyl chloroformate, sodium thiocyanate and o-phenylenediamine as raw materials.
[0004] In the prior art, a conventional catalyst is directly added to carry out a catalytic reaction during the synthesis of methyl thiophanate, and the reaction process is relatively violent, which not only easily causes liquid splashing, but also increases the generation of side reactions, resulting in a decrease in the yield and purity of the methyl thiophanate product.
[0005] Based on this, the present invention provides a catalyst for synthesizing methyl thiophanate to solve the corresponding problem. Summary of the invention
[0006] In view of the problems in the prior art, the present invention provides a catalyst for synthesizing methyl thiophanate.
[0007] The technical solution adopted by the present invention to solve the technical problem is: a catalyst for synthesizing methyl thiophanate, comprising a carrier and an active component;
[0008] The carrier is a pretreated zeolite;
[0009] The BET specific surface area of the carrier is 120-150 m 2 / g;
[0010] The pore volume of the carrier is 0.5-0.7 mL / g;
[0011] Calculated on the basis of the mass of the carrier, the content of the active component is 0.1-2 g / 30 g.
[0012] As a further technical solution: the carrier preparation method is:
[0013] First, tetraethylammonium hydroxide was added to deionized water and stirred for 10 minutes, then sodium hydroxide was added and stirred for 15 minutes, and then sodium aluminate was added and stirred for 10 minutes to obtain an intermediate solution;
[0014] Add silica sol to the intermediate solution, stir for 35 minutes at room temperature, then add β-zeolite powder, continue stirring for 4 hours, and let stand for 2 hours to obtain a composite gel;
[0015] The obtained composite gel was dried for 15 hours to obtain a solidified product;
[0016] The obtained solidified material was placed in a muffle furnace, gradually heated to 560°C, calcined for 12 hours, and cooled to room temperature to obtain a calcined material;
[0017] The calcined material was added to the ammonium citrate solution, refluxed and stirred for 4 hours, then taken out and added to water, refluxed and stirred for 30 minutes, filtered, dried, placed in a Maboise furnace, gradually heated to 520°C, calcined for 5 hours, and cooled to room temperature to obtain.
[0018] As a further technical solution: wherein the molar ratio of silicon dioxide, aluminum oxide, tetraethylammonium hydroxide and sodium hydroxide in the composite gel is: 1-1.2:0.8-1:0.2-0.3:0.1-0.15.
[0019] As a further technical solution: the drying temperature is 65° C. and the drying time is 10 hours.
[0020] As a further technical solution: the heating rate in the horse-boiling furnace is 5°C / min.
[0021] As a further technical solution: the mixing ratio of the calcined material and the ammonium citrate solution is 12-15g:150mL;
[0022] The mass fraction of ammonium citrate solution is 10%.
[0023] As a further technical solution: the preparation method of the active component:
[0024] First, benzyl chloride and triethylamine are added to the solvent in sequence, stirred for 20 minutes, and then the temperature is adjusted to 80°C, and the reaction is stirred and reacted for 2 hours. Then, a crystallizing agent is added, and the temperature of the reaction system is adjusted to 5°C, and the reaction is kept warm and crystallized for 1 hour. Then, the crude product is filtered to obtain a crude product, which is washed, separated from the solid and the liquid, and vacuum dried to obtain;
[0025] The vacuum drying temperature is 60°C and the time is 8 hours.
[0026] As a further technical solution: the molar ratio of benzyl chloride to triethylamine is 1:1;
[0027] The solvent is ethyl acetate;
[0028] The crystallization agent is acetonitrile;
[0029] The mass ratio of the benzyl chloride to the solvent is 1:10;
[0030] The mass ratio of the crystallization agent to the solvent is 1:3.
[0031] A method for preparing a catalyst for synthesizing thiophanate-methyl comprises the following steps:
[0032] (1) adding the active component to the solvent and mixing them uniformly to obtain an active component solution;
[0033] (2) mixing the carrier and the active component, using nitrogen as a protective gas, stirring at 30° C. for 2 hours, and then removing the solvent by rotary evaporation under vacuum conditions to obtain;
[0034] The vacuum degree of the vacuum condition is 0.2Pa.
[0035] Synthesis mechanism of methyl thiophanate, catalytic synthesis by catalyst:
[0036] a: Thiocyanation reaction:
[0037]
[0038] b: Condensation reaction:
[0039]
[0040] Beneficial effects of the present invention:
[0041] The catalyst for synthesizing methyl thiophanate prepared by the invention can promote the reaction to proceed mildly, and can improve the reaction effect between methyl chloroformate, sodium thiocyanate and o-phenylenediamine raw materials, thereby greatly shortening the synthesis cycle of methyl thiophanate. The methyl thiophanate synthesized by using the catalyst prepared by the invention has high purity and relatively low side reactions.
[0042] The catalyst prepared by the present invention can release the active component stably and continuously during the reaction by combining the carrier with the active component, thereby avoiding the instantaneous catalytic reaction of a large amount of active components, resulting in violent reaction, easy liquid splashing, and may also cause more side reactions, greatly reducing the yield and purity of the product.
[0043] The catalyst prepared by the present invention can adsorb reactant molecules and make them in a more stable structural state to continuously react under the catalysis of active components, continuously promoting the reaction, thereby improving the sustainability and stability of the entire reaction and improving the yield of the product. DETAILED DESCRIPTION
[0044] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.
[0045] Example 1
[0046] A catalyst for synthesizing methyl thiophanate, comprising a carrier and an active component;
[0047] The carrier is a pretreated zeolite;
[0048] The BET specific surface area of the carrier is 125.2 m 2 / g;
[0049] The pore volume of the carrier is 0.55 mL / g;
[0050] Calculated on the basis of the mass of the carrier, the content of the active component is 1.2 g / 30 g.
[0051] The method for preparing the carrier is:
[0052] First, tetraethylammonium hydroxide was added to deionized water and stirred for 10 minutes, then sodium hydroxide was added and stirred for 15 minutes, and then sodium aluminate was added and stirred for 10 minutes to obtain an intermediate solution;
[0053] Add silica sol to the intermediate solution, stir for 35 minutes at room temperature, then add β-zeolite powder, continue stirring for 4 hours, and let stand for 2 hours to obtain a composite gel;
[0054] The obtained composite gel was dried for 15 hours to obtain a solidified product;
[0055] The obtained solidified material was placed in a muffle furnace, gradually heated to 560°C, calcined for 12 hours, and cooled to room temperature to obtain a calcined material;
[0056] The calcined material was added to the ammonium citrate solution, refluxed and stirred for 4 hours, then taken out and added to water, refluxed and stirred for 30 minutes, filtered, dried, placed in a Maboise furnace, gradually heated to 520°C, calcined for 5 hours, and cooled to room temperature to obtain.
[0057] Wherein, the molar ratio of silicon dioxide, aluminum oxide, tetraethylammonium hydroxide and sodium hydroxide in the composite gel is 1:0.8:0.2:0.1.
[0058] The drying temperature is 65°C and the drying time is 10 h.
[0059] The heating rate in the Ma Fuel Furnace is 5℃ / min.
[0060] The mixing ratio of calcined material and ammonium citrate solution is 12g:150mL;
[0061] The mass fraction of ammonium citrate solution is 10%.
[0062] Active ingredient preparation method:
[0063] First, benzyl chloride and triethylamine are added to the solvent in sequence, stirred for 20 minutes, and then the temperature is adjusted to 80°C, and the reaction is stirred and reacted for 2 hours. Then, a crystallizing agent is added, and the temperature of the reaction system is adjusted to 5°C, and the reaction is kept warm and crystallized for 1 hour. Then, the crude product is filtered to obtain a crude product, which is washed, separated from the solid and the liquid, and vacuum dried to obtain;
[0064] The vacuum drying temperature is 60°C and the time is 8 hours.
[0065] The molar ratio of benzyl chloride to triethylamine is 1:1;
[0066] The solvent is ethyl acetate;
[0067] The crystallization agent is acetonitrile;
[0068] The mass ratio of the benzyl chloride to the solvent is 1:10;
[0069] The mass ratio of the crystallization agent to the solvent is 1:3.
[0070] Example 2
[0071] The difference from the technical solution of embodiment 1 is:
[0072] The method for preparing the carrier is:
[0073] First, tetraethylammonium hydroxide was added to deionized water and stirred for 10 minutes, then sodium hydroxide was added and stirred for 15 minutes, and then sodium aluminate was added and stirred for 10 minutes to obtain an intermediate solution;
[0074] Add silica sol to the intermediate solution, stir for 35 minutes at room temperature, then add β-zeolite powder, continue stirring for 4 hours, and let stand for 2 hours to obtain a composite gel;
[0075] The obtained composite gel was dried for 15 hours to obtain a solidified product;
[0076] The obtained solidified material was placed in a muffle furnace, gradually heated to 560°C, calcined for 12 hours, and cooled to room temperature to obtain a calcined material;
[0077] The calcined material was added to the ammonium citrate solution, refluxed and stirred for 4 hours, then taken out and added to water, refluxed and stirred for 30 minutes, filtered, dried, placed in a Maboise furnace, gradually heated to 520°C, calcined for 5 hours, and cooled to room temperature to obtain.
[0078] Wherein, the molar ratio of silicon dioxide, aluminum oxide, tetraethylammonium hydroxide and sodium hydroxide in the composite gel is: 1.1:0.9:0.26:0.14.
[0079] The drying temperature is 65°C and the drying time is 10 h.
[0080] The heating rate in the Ma Fuel Furnace is 5℃ / min.
[0081] The mixing ratio of calcined material and ammonium citrate solution is 13g:150mL;
[0082] The mass fraction of ammonium citrate solution is 10%.
[0083] Example 3
[0084] The difference from the technical solution of embodiment 1 is:
[0085] The method for preparing the carrier is:
[0086] First, tetraethylammonium hydroxide was added to deionized water and stirred for 10 minutes, then sodium hydroxide was added and stirred for 15 minutes, and then sodium aluminate was added and stirred for 10 minutes to obtain an intermediate solution;
[0087] Add silica sol to the intermediate solution, stir for 35 minutes at room temperature, then add β-zeolite powder, continue stirring for 4 hours, and let stand for 2 hours to obtain a composite gel;
[0088] The obtained composite gel was dried for 15 hours to obtain a solidified product;
[0089] The obtained solidified material was placed in a muffle furnace, gradually heated to 560°C, calcined for 12 hours, and cooled to room temperature to obtain a calcined material;
[0090] The calcined material was added to the ammonium citrate solution, refluxed and stirred for 4 hours, then taken out and added to water, refluxed and stirred for 30 minutes, filtered, dried, placed in a Maboise furnace, gradually heated to 520°C, calcined for 5 hours, and cooled to room temperature to obtain.
[0091] Wherein, the molar ratio of silicon dioxide, aluminum oxide, tetraethylammonium hydroxide and sodium hydroxide in the composite gel is 1.2:1:0.3:0.15.
[0092] The drying temperature is 65°C and the drying time is 10 h.
[0093] The heating rate in the Ma Fuel Furnace is 5℃ / min.
[0094] The mixing ratio of calcined material and ammonium citrate solution is 15g:150mL;
[0095] The mass fraction of ammonium citrate solution is 10%.
[0096] Comparative Example 1:
[0097] On the basis of Example 1, the carrier is replaced with activated carbon, and the rest of the technical solutions remain unchanged.
[0098] Comparative Example 2:
[0099] On the basis of Example 1, only the active component is used without the carrier, and the rest of the technical scheme remains unchanged.
[0100] test
[0101] Using methyl chloroformate, sodium thiocyanate and o-phenylenediamine as raw materials, according to a certain ratio, in the presence of solvent ethyl acetate and a catalyst, a synthetic reaction is performed to obtain methyl thiophanate product;
[0102] The molar ratio of methyl chloroformate to sodium thiocyanate is 1.03:1;
[0103] The molar ratio of o-phenylenediamine and sodium thiocyanate is 0.48:1:
[0104] The catalysts of the examples and comparative examples were tested:
[0105] The amount of catalyst added is 8% of the total raw material mass:
[0106] Table 1
[0107]
[0108]
[0109] It can be seen from Table 1 that the methyl thiophanate synthesis reaction using the catalyst prepared by the present invention is more gentle.
[0110] The yield of catalyzing the synthesis of methylthiophanate by the catalysts of the examples and comparative examples;
[0111] Table 2
[0112] Yield % Example 1 99.3 Example 2 99.1 Example 3 99.6 Comparative Example 1 94.2 Comparative Example 2 90.0
[0113] It can be seen from Table 2 that the yield of methylthiophanate synthesis catalyzed by the catalyst prepared by the present invention is higher.
[0114] The properties of thiophanate-methyl synthesized by the catalysts prepared in the examples and comparative examples were observed and compared;
[0115] Table 3
[0116]
[0117]
[0118] As can be seen from Table 3, the methyl thiophanate synthesized by the catalyst of the present invention is colorless prismatic crystals.
[0119] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A catalyst for the synthesis of thiophanate-methyl, characterized in that including a carrier and an active component; The carrier is a pretreated zeolite; The BET specific surface area of the carrier is 120-150 m 2 / g; The pore volume of the carrier is 0.5-0.7 mL / g; Calculated on the basis of the mass of the carrier, the content of the active component is 0.1-2 g / 30 g.
2. A catalyst for synthesis of thiophanate-methyl according to claim 1, characterized in that: The carrier preparation method is: First, tetraethylammonium hydroxide was added to deionized water and stirred for 10 minutes, then sodium hydroxide was added and stirred for 15 minutes, and then sodium aluminate was added and stirred for 10 minutes to obtain an intermediate solution; Add silica sol to the intermediate solution, stir for 35 minutes at room temperature, then add β-zeolite powder, continue stirring for 4 hours, and let stand for 2 hours to obtain a composite gel; The obtained composite gel was dried for 15 hours to obtain a solidified product; The obtained solidified material was placed in a muffle furnace, gradually heated to 560°C, calcined for 12 hours, and cooled to room temperature to obtain a calcined material; The calcined material was added to the ammonium citrate solution, refluxed and stirred for 4 hours, then taken out and added to water, refluxed and stirred for 30 minutes, filtered, dried, placed in a Maboise furnace, gradually heated to 520°C, calcined for 5 hours, and cooled to room temperature to obtain.
3. A catalyst for synthesis of thiophanate-methyl according to claim 2, characterized in that: in, The molar ratio of silicon dioxide, aluminum oxide, tetraethylammonium hydroxide and sodium hydroxide in the composite gel is 1-1.2:0.8-1:0.2-0.3:0.1-0.
15.
4. A catalyst for synthesis of thiophanate-methyl according to claim 2, characterized in that: The drying temperature is 65° C. and the drying time is 10 h.
5. A catalyst for synthesis of thiophanate-methyl according to claim 2, characterized in that: The heating rate in the horse-boiling furnace is 5°C / min.
6. A catalyst for synthesis of thiophanate-methyl according to claim 2, characterized in that: The mixing ratio of the calcined material and the ammonium citrate solution is 12-15 g: 150 mL; The mass fraction of ammonium citrate solution is 10%.
7. A catalyst for synthesis of thiophanate-methyl according to claim 1, characterized in that: The active component preparation method: First, benzyl chloride and triethylamine are added to the solvent in sequence, stirred for 20 minutes, and then the temperature is adjusted to 80°C, and the reaction is stirred and reacted for 2 hours. Then, a crystallizing agent is added, and the temperature of the reaction system is adjusted to 5°C, and the reaction is kept warm and crystallized for 1 hour. Then, the crude product is filtered to obtain a crude product, which is washed, separated from the solid and the liquid, and vacuum dried to obtain; The vacuum drying temperature is 60°C and the time is 8 hours.
8. A catalyst for synthesis of thiophanate-methyl according to claim 7, characterized in that: The molar ratio of benzyl chloride to triethylamine is 1:1; The solvent is ethyl acetate; The crystallization agent is acetonitrile; The mass ratio of the benzyl chloride to the solvent is 1:10; The mass ratio of the crystallization agent to the solvent is 1:
3.
9. A method for preparing a catalyst for synthesizing thiophanate-methyl according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) adding the active component to the solvent and mixing them uniformly to obtain an active component solution; (2) mixing the carrier and the active component, using nitrogen as a protective gas, stirring at 30° C. for 2 hours, and then removing the solvent by rotary evaporation under vacuum conditions to obtain; The vacuum degree of the vacuum condition is 0.2Pa.